Role conflict and performance of part time students in Indonesia: The effect of burnout, coping behavior and spiritual intelligence - Nirmalasari , Leli; Minai, Minai (Annals of Management and Organization Research, 2023)
Purpose: This study examined the relationship between role conflict and the performance of part-time students in Indonesia, with a focus on the effects of burnout, coping behavior, and spiritual intelligence. Research methodology: The study tested performance, academic performance, and work performance, with extreme work stress (burnout) positioned as the mediating factor, and coping and spiritual intelligence positioned as moderating variables. Results: This study found that role conflict negatively affects the academic and work performance of part-time students, and burnout mediates this relationship. Coping behavior and spiritual intelligence moderate the relationship between role conflict and performance. Limitations: Within the context of demographic factors, some authors, such as Waskito (2019), Kastaman and Coralia (2022), and Wardani and Pitensah (2021), suggest examining the effect of factors such as age and ethnic groups. Thus, in future studies, it is advisable to review the effects of demographic factors such as age, ethnicity, and income level. Contribution: This study contributes to the existing literature by providing a new perspective on the performance of part-time students and highlights the importance of considering role conflict and its effects on their performance.